Diabetes research reported by nurses in Nordic countries. Issue 2 (15th July 2013) - Graue, M; Iversen, MM; Sigurdardottir, ÁK; Zoffmann, V; Smide, B; Leksell, J
Abstract: New knowledge from research studies is important as a foundation for high‐quality care in practice as well as crucial to further stimulate research in the future. The aims of this study were to determine the total number of peer‐reviewed articles on diabetes research reported by nurses in four Nordic countries (Denmark, Iceland, Norway and Sweden) from 1979–2009, and to identify the time periods in which they had been published, different study designs and the number of publications related to nurse authors. We performed an electronic search for potentially relevant scientific articles between 1 January 1979 and 31 December 2009 using the MEDLINE, Medline in process, EMBASE, CINAHL, PsycINFO and Cochrane databases. The studies focused either on the diabetes population or on diabetes health care professionals. We included 164 scientific articles; 132 resulting from electronic search and 32 from manual search. They were published in 63 different scientific journals, with 52 (32%) published in nursing journals and typically by authors with university degrees. Only one in four authors had published five or more articles. The majority of the studies originated from a single country, with 23 (14%) including co‐authors from another country. It was concluded that research in diabetes reported by nurses has increased considerably after the year 2000. Further action is needed to build stronger national groups of researchers. International collaborative research networks facilitate funding opportunities and contribute to further development of professional research competence. Copyright © 2013 FEND. Published by John Wiley & Sons, Ltd.